2022
DOI: 10.3389/fmolb.2022.974156
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of ferroptosis in glioblastoma: Therapeutic opportunities and challenges

Abstract: Glioblastoma (GBM) is the most common malignant craniocerebral tumor. The treatment of this cancer is difficult due to its high heterogeneity and immunosuppressive microenvironment. Ferroptosis is a newly found non-apoptotic regulatory cell death process that plays a vital role in a variety of brain diseases, including cerebral hemorrhage, neurodegenerative diseases, and primary or metastatic brain tumors. Recent studies have shown that targeting ferroptosis can be an effective strategy to overcome resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 174 publications
0
10
0
Order By: Relevance
“…In addition to showcasing the sensitivity of gbmMINER in delineating disease-driving mechanisms in a small subgroup of patients within a larger cohort, this finding also underscores generalizability of the mechanisms by which IDH1 acts through a combinatorial network to activate ferroptosis. While there is evidence in literature that both IDH1 and TP53 regulate ferroptosis, the primary mechanism was unknown 72 . In fact, a recent study discovered that although the acetylation-defective mutant TP53 3KR lost its ability to induce cell senescence, apoptosis, and cell-cycle arrest, it was still able to inhibit tumorigenesis by inducing ferroptosis 73 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to showcasing the sensitivity of gbmMINER in delineating disease-driving mechanisms in a small subgroup of patients within a larger cohort, this finding also underscores generalizability of the mechanisms by which IDH1 acts through a combinatorial network to activate ferroptosis. While there is evidence in literature that both IDH1 and TP53 regulate ferroptosis, the primary mechanism was unknown 72 . In fact, a recent study discovered that although the acetylation-defective mutant TP53 3KR lost its ability to induce cell senescence, apoptosis, and cell-cycle arrest, it was still able to inhibit tumorigenesis by inducing ferroptosis 73 .…”
Section: Discussionmentioning
confidence: 99%
“…The potent anti-stemness influence of DE-FeONPs is attributed to inhibiting ALDH1A1 and inducing lipid peroxidation-dependent ferroptosis ( Abu-Serie, 2024 ). Since, the balance between reactive radical species and antioxidants is primarily responsible for therapeutic resistance in GBM ( Zhuo et al, 2022 ), inducing ferroptosis could be one of the most promising treatments ( Luo et al, 2022 ; Xue et al, 2024 ). Notably, GSCs have a higher capacity than normal brain cells for iron uptake by upregulating the expression of its receptor ( Park et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These novel cell death pathways including the accumulated copper-mediated cuproptosis and iron-mediated ferroptosis, lead to mitochondrial dysfunction and uncontrolled lipid peroxidation, respectively ( Tang et al, 2021 ; Abu-Serie, 2023 ; Abu-Serie and Abdelfattah, 2023 ). Ferroptosis inducers can thus improve sensitivity of GBM to chemotherapeutic drugs (e.g., TMZ), radiation, and immunotherapy as well as targeted therapy (e.g., epidermal growth factor receptor inhibitors) and inhibit metastasis ( Zhuo et al, 2022 ; Bo et al, 2024 ; Wang et al, 2024 ). Ferroptosis is exacerbated by the inhibition of the antioxidant glutathione system, including glutathione peroxidase (GPX)4 and its substrate glutathione (GSH) ( Koppula et al, 2021 ; Zhuo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances have identified that the hub genes of ferroptosis pathway, including cysteine-glutamate transporter (xCT) and glutathione peroxidase (GPX), play indispensable roles in the therapeutic resistance of tumors, especially for GBM [14] , [15] , [16] . Intervention of these key factors is proved to enhance the sensitivity of chemotherapy and radiotherapy, thus improving the prognosis of GBM [17] , [18] . Erastin (ERA) is the first small molecule inhibitor found to selectively and effectively mediate ferroptosis through xCT, voltage-dependent anion channel (VDAC) and p53.…”
Section: Introductionmentioning
confidence: 99%